Matters of Taste: Kant’s Epistemological Aesthetics - Papp, Zoltán (Con-Textos Kantianos. International Journal of Philosophy, 2020)
This paper is concerned with what I believe is the epistemological mission of Kant’s doctrine of taste. The third Critique inherits two problems from the first. The evident one is that the categorial constitution of nature must be complemented with the notion of purposiveness. The less evident one is that the transcendental theory of experience needs a common sense in order to secure a common objectivity. The judgment of taste, conceived of by Kant as a ‘cognition in general’ not restricted to either the particular subject or the particular object, offers a solution. It turns out to be a judgment that cannot be made without assuming the purposiveness of nature and the uniformity of the cognizing subjects.